Psychological Distress and Trust in University Management Among International Students During the COVID-19 Pandemic - Khan, Karamat; Li, Yanyan; Liu, Sheng; Li, Chuntao (Frontiers in Psychology, 2021)
Since the end of 2019, the outbreak of the COVID-19 pandemic has engendered widespread fear and anxiety across China. Nearly half a million international students pursuing their studies in Chinese universities have also been exposed to the psychological distress triggered by the unfolding crisis. In addition to government and medical institutions’ efforts, universities have also endeavored to mitigate concerns among these students under quarantine on campus by providing reliable information as well as medical, monetary, and emotional support. In this study, international students’ trust in university management teams and its role in remediating their anxieties were evaluated using an online survey conducted after 10 days of the lockdown of Wuhan, China. The empirical analysis incorporates quantitative data from 180 international students. Ordinary least squares regression and probit regression were used in the analysis with the non-robust and robust models. The study found students’ perception of trust in university management to be negatively associated with their anxiety levels. Additionally, having trust in university management was found to positively influence students’ commitment to the self-quarantine guidelines. These results reinforce the important role of universities and their relationship with international students during public health emergencies.